A multivariable optimization of a Brayton power cycle operating with CO2 as working fluid. (1st October 2016) - Battisti, Felipe G.; Cardemil, José M.; da Silva, Alexandre K.
Abstract: This article simulates and optimizes a CO2 -based Brayton cycle having one re-heating stage and one recuperator such that the exergetic efficiency, normalized by the cycle's overall global conductance, ηII /(UA)Total, is maximized. In total, six operational parameters are simultaneously optimized for the cycle, which are: the heat source temperature, the CO2 's highest temperature, the CO2 's highest and lowest pressure values, and the heat source's mass flow rates directed to the heater and re-heater. For that, a dedicated thermodynamic routine was implemented and coupled to a property database, which was able to account for the large variation of thermophysical properties near the critical point, along with a hybrid optimization routine. The optimization process showed that the normalized exergetic efficiency was highly affected by all parameters considered, and that a pronounced global maximum is obtainable with respect to all optimization variables, except the heat source temperature. The trends obtained not only confirm the importance of the optimization process proposed, but also permitted the development of a direct relation between the normalized exergetic efficiency and the heat source temperature. Additionally, the results suggest the existence of an optimal total global conductance for the cycle, which serves as a scale for the power plant. Highlights: Optimal operational conditions and scale of a Brayton cycle. Global conductance normalized exergetic efficiency. Globally maximized performance of a Brayton cycle operating with CO2 .